Population Studies of Tree Hole Breeding Aedes Species (Diptera: Culicidae) in Dhaka University Campus and its Adjacent Suhrawardi Park, Dhaka City, Bangladesh (Bangladesh Journal of Zoology, 2012)
A survey of the larval population of tree hole breeding Aedes mosquito was conducted from January to December, 2010 in four different areas of Dhaka University Campus and its adjacent Suhrawardi park. A total of 689 mosquito larvae was collected during the survey. Among them 396 (57.47%) were Aedes albopictus, 51 (7.02%) were Ae. aegypti and 242 (35.12%) other Aedes species, and the number of male and female among them was counted 347 (50.36%) and 342 (49.63%), respectively. Among the varieties of plant species in the study area only 27 species of trees were found with 56 holes wherein 34 holes of 17 species trees were used by mosquitoes for breeding ground. The highest number (160) of larvae was found in bamboo (Bambusa nutans) stumps hole and lowest (13) in Delonix regia hole. The highest number of larval population was collected in September and the larval population increased from March to September and then gradually decreased. No mosquito larva was found in the tree holes in January and February. The number of larvae collected from different survey areas also varied which were 309 (44.84%), 152 (22.06%), 145 (21.04%) and 83 (12.04%) in Suhrawardi park, and the Arts building, Curzon hall and Botanical garden of Dhaka University, respectively. DOI: http://dx.doi.org/10.3329/bjz.v40i1.12887 Bangladesh J. Zool. 40(1): 1-11, 2012